Artificial Intelligence and Administrative Justice: An Analysis of Predictive Justice in France - Nouri, Zouhaier; Salah, Walid Ben; AlOmran, Nayel (Faculty of Law, Hasanuddin University, 2024)
This article critically analyzes the ethical and legal implications of adopting predictive analytics by the French administrative justice system. It raises a key question: Is it wise to integrate artificial intelligence into the administrative justice system, considering its potential benefits, despite the associated risks, ethical dilemmas, and legal challenges? The research employs a method based on an extensive literature review, a qualitative analysis of the adoption by the French administrative justice of predictive analytics tools, and a critical evaluation of the benefits and issues these tools bring. The study finds that AI can make the administrative justice system more efficient, reduce backlogs, and enhance the consistency and predictability of judicial decisions. However, the study also identifies important risks and serious ethical and legal issues associated with integrating AI tools into the justice system. Especially, AI utilization can lead to the dehumanization of justice and poses real risks to the independence and impartiality of justice. While AI can offer significant benefits to all the stakeholders of the administrative justice system, its integration must be approached with caution. A progressive and responsible approach to AI adoption is necessary to avoid compromising judicial integrity and upholding fundamental justice values.